The Phenomenon of Learning at Co-Working Space Cafes (a Case Study of UMS Students Between Needs and Lifestyle) - Galeh Aprilia; Agus Susilo (The Innovation of Social Studies Journal, 2026)
The development of digital technology has shifted UMS students’ learning patterns toward co-working  spaces as flexible environments supporting both academic needs and modern lifestyles. This study aims to examine the phenomenon of using co-working  spaces as alternative learning environments among students at Universitas Muhammadiyah Surakarta (UMS), focusing on two main aspects: academic needs and lifestyle. A qualitative descriptive approach with a case study method was employed. Data were collected through in-depth interviews with students who actively use co-working  spaces, as well as direct observations at several locations in Surakarta. The findings reveal that the primary motivations for students choosing co-working  spaces include comfort, reliable Wi-Fi access, and a conducive atmosphere that supports focused learning. In addition to positively influencing academic productivity, co-working  spaces have become part of the modern student lifestyle, emphasizing aesthetics, digital presence, and contemporary trends. Social factors, such as peer support and collaborative study habits, also play a significant role in shaping their preferences. These findings indicate that co-working  spaces serve not only as facilities to fulfill academic needs but also as social spaces representing identity and lifestyle in the digital age. This study contributes to understanding the shift in student learning patterns and its implications for the development of educational facilities in higher education institutions.